Iterating ‘addiction’: Residential relocation and the spatio-temporal production of alcohol and other drug consumption patterns - Dilkes-Frayne, E.; Fraser, Suzanne; Pienaar, Kiran; Kokanovic, R. (Elsevier BV, 2017)
Addiction is generally understood to be characterised by a persistent pattern of regular, heavy alcohol and other drug consumption. Current models of addiction tend to locate the causes of these patterns within the body or brain of the individual, sidelining relational and contextual factors. Where space and place are acknowledged as key factors contributing to consumption, they tend to be conceived of as static or fixed, which limits their ability to account for the fluid production and modulation of consumption patterns over time. In this article we query individualised and decontextualised understandings of the causes of consumption patterns through an analysis of accounts of residential relocation from interviews undertaken for a large research project on experiences of addiction in Australia. In conducting our analysis we conceptualise alcohol and other drug consumption patterns using Karen Barad's notions of intra-action and spatio-temporality, which allow for greater attention to be paid to the spatial and temporal dimensions of the material and social processes involved in generating consumption patterns. Drawing on 60 in-depth interviews conducted with people who self-identified as experiencing an alcohol and other drug addiction, dependence or habit, our analysis focuses on the ways in which participant accounts of moving enacted space and time as significant factors in how patterns of consumption were generated, disrupted and maintained. Our analysis explores how consumption patterns arose within highly localised relations, demonstrating the need for understandings of consumption patterns that acknowledge the indivisibility of space and time in their production. In concluding, we argue for a move away from static conceptions of place towards a more dynamic conception of spatio-temporality, and suggest the need to consider avenues for more effectively integrating place and time into strategies for generating preferred consumption patterns and initiating and sustaining change where desired.